Fair play? Reading between White lines at South African school sports days - Truyts, Carina (Acta Academica: Critical views on society, culture and politics, 2018)
In the spirit of Max Gluckmans’s 1940 ‘The Bridge’ paper, this paper offers a situational analysis of the Kylemore versus Groendal High School Derby Day in the Western Cape’s Dwars River valley in 2014. I compare this Derby Day with an athletic event at my Former Model C (Whites-only during apartheid) school in 2004. Situational analysis allows us to track persistent racial disparities over time and ask how time is figured differentially in relation to belonging. I show how historically contingent stereotypes of Coloured people were actively gainsaid, and subjectivities that are subversive and plural were enacted at the former. At Sutherland High where pupils ‘reach for the stars’ by drawing on a repertoire of colonial tools of distinction, the future was optimised in reference to the ‘rainbow nation’. In both cases symbols of modernity were drawn on in the practice of enacting belonging. These sites share a foundational logic that operates differentially, maintaining and creating unequal terrain for play. This logic can be observed by considering and questioning White lines and the iterative process of drawing, ignoring, and challenging them.